Efficient implementation of the non-Dyson third-order algebraic diagrammatic construction approximation for the electron propagator for closed- and open-shell molecules - Dempwolff, Adrian; Schneider, Matthias; Hodecker, Manuel; Dreuw, Andreas (The journal of chemical physics, 2019)
A novel efficient implementation of the non-Dyson algebraic diagrammatic construction (ADC) scheme of the (N − 1)-part of the electron propagator up to third order of perturbation theory is presented. Due to the underlying spin-orbital formulation, for the first time, the computation of ionization potentials of open-shell radicals is thus possible via non-Dyson ADC schemes. Thorough evaluation of the accuracy, applicability, and capabilities of the new method reveals a mean error of 0.15 eV for closed- as well as open-shell atoms and molecules.
Gesehen am 30.07.2019